Religious Extremism as Symbolic Domination: Mosque Communities and Socio-Economic Reconstruction in Sub-Saharan Africa - Amada Talikoa (UIN Sunan Gunung Djati Bandung, 2026)
This study examines religious extremism in conflict-affected societies in Sub-Saharan Africa as a form of symbolic domination within the religious field and explores the extent to which local religious communities can contribute to socio-economic reconstruction. This study employs a qualitative, document-based approach. Data were collected through the analysis of African liberation theology literature, studies on religious extremism in Africa, official reports from international institutions, and selected credible online media sources. The data were analyzed using thematic-critical analysis, with particular attention to the concepts of symbolic domination, habitus, field, symbolic capital, and community-based social reconstruction. The study finds that religious extremism operates not only through physical violence but also through symbolic domination, whereby extremist actors seek to monopolize religious interpretation, legitimize violence, and reshape collective dispositions under conditions of poverty, exclusion, and state fragility. The study also shows that extremism deepens structural suffering by disrupting livelihoods, weakening solidarity, and paralyzing grassroots survival creativity. At the same time, the religious field remains open to contestation, and mosque-based communities may serve as spaces of resistance, moral protection, peacebuilding, and socio-economic recovery. These findings suggest that efforts to prevent violent extremism should move beyond military and security-centered approaches by strengthening local religious communities as social and economic actors. The study contributes to ongoing debates on religion and violence by highlighting the importance of community-based religious infrastructures in promoting resilience, rehabilitation, and bottom-up reconstruction in conflict-affected settings.